PENGARUH PENAMBAHAN STARTER TERHADAP KARAKTERISTIK PROSES PENGOMPOSAN DAN KUALITAS KOMPOS LIMBAH PABRIK AGAR - Firman L. Sahwan (Jurnal Teknologi Lingkungan, 2010)
Solid waste from â€œagar-agarâ€ (gelation made of seaweed) factory in huge amount and hasÂ potency to pollute the environment if it is not well managed, obviously has opportunityÂ to be used as compost. The purpose of this research is to find out the characteristic ofÂ composting process of agar-agar factoryâ€™s waste, and the quality of its compost product,based on 2 ( two ) treatments i.e. with and without the use chicken manure starter. InÂ general, result of the research showing that there is no significant different betweenÂ using chicken manure starter and not using chiken manure starter, with understandingÂ that both composting process can be done in aerobic condition (normal) with compostÂ quality according to mature compost criteria. However, specifically the rate of wasteÂ decomposition (composting process) of using chicken manure starter looks faster inÂ initial period of decomposition.Key words : compost, â€œagar-agarâ€ factory waste, chiken manure starter.